Salmonella brain abscess in an infant - Samal Badhuli; Oommen Seema; Swami Anjali; Maskey Madhavi; Shastri Jayanthi (Wolters Kluwer Medknow Publications, 2009)
Brain abscess is an uncommon and serious life-threatening infection in children. Focal intracranial infections caused by Salmonella spp. in this age group are also rare. We report the case of a 4-month-old male infant with a frontoparietal brain abscess caused by Salmonella typhimurium , the presence of which was not suspected clinically.